Bifunctional chalcogen linkers for the stepwise generation of multimetallic assemblies and functionalized nanoparticles - Robson,JA; Gonzàlez,de Rivera F; Jantan,KA; Wenzel,MN; White,AJ; Rossell,O; Wilton-Ely,JD (Inorganic Chemistry, 2016)
The disulfide ligand (SC6H4CO2H-4)2 acts as a simple but versatile linker for a range of group 8 transition metals through reaction of the oxygen donors. This leads to a range of homobimetallic ruthenium and osmium alkenyl compounds, [{M(CHCHR)(CO)(PPh3)2(O2CC6H4S-4)}2] (M = Ru, Os; R = C6H4Me-4). Additional metal-based functionality can be added through the use of precursors incorporating rhenium bipyridine units (R = (bpy)ReCl(CO)3). The more robust diphosphine ligands in [{Ru(dppm)2(O2CC6H4S-4)}2](2+) (dppm = diphenylphosphinomethane) allow reduction of the disulfide bond with sodium borohydride to yield the thiol complex [Ru(O2CC6H4SH-4)(dppm)2](+). This complex reacts with [AuCl(PPh3)] to afford the bimetallic compound [Ru(dppm)2(O2CC6H4S-4)Au(PPh3)](+). However, an improved route to the same and related heterobimetallic compounds is provided by the reaction of cis-[RuCl2(dppm)2] with [Au(SC6H4CO2H-4)(L)] (L = PPh3, PCy3, PMe3, IDip) in the presence of base and NH4PF6 (IDip = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene). The heterotrimetallic compound [Au(SC6H4CO2Ru(dppm)2)2](+) is accessible through the reaction of the homoleptic gold(I) dithiolate [Au(SC6H4CO2H-4)2]PPN (PPN = bis(triphenylphosphine)iminium) with cis-[RuCl2(dppm)2]. Without departure from the same methodology, greater complexity can be incorporated into the system to provide the penta- and heptametallic assemblies [(dppf){AuSC6H4CO2Ru(dppm)2}2](2+) and [(dppf){AuSC6H4CO2Os(CHCH-bpyReCl(CO)3)(CO)(PPh3)2}2]. The same stepwise approach provides the dinuclear organometallic complexes [(L)Au(SC6H4CO2-4)M(CHCHC6H4Me-4)(CO)(PPh3)2] (M = Ru, Os; L = PPh3, IDip). Complexes containing three metals from different groups of the periodic table [(L)Au(SC6H4CO2-4)M{CHCH-bpyReCl(CO)3}(CO)(PPh3)2] (M = Ru, Os) can also be prepared, with one ruthenium example (L = PPh3) being structurally characterized. In order to illustrate the versatility of this approach, the synthesis and characterization (IR and